The Efficacy of Flupentixol-Melitracen in the Adjuvant Therapy of Ulcerative Colitis in the Chinese Population: A Meta-Analysis - Xiaoqian Zhou; Lei Zhao; Ping Yang; Yaxi Chen; Xiong Z. Ruan (Gastroenterology Research and Practice)
Objectives. Our aim of this study is to compare the efficacy of flupentixol-melitracen in the adjuvant therapy of ulcerative colitis patients in the Chinese population. Methods. Both the RevMan 5.2 and the Stata 12.0 software are used in this study for analysis, and a fixed-effect model (the Mantel-Haenszel method) or a random-effect model (the DerSimonian and Laird method) is used to merge or aggregate the risk ratio (RR) and its 95% confidence intervals (CI) of included studies. Results. Eleven trials involving 654 ulcerative colitis patients (treated group: 328; control group: 326) were analyzed in this study. Significant differences (RR=1.29, 95% CI=1.20 to 1.40, P<0.001) between patients were observed between the two groups. Conclusions. Our results suggested that the efficacy of flupentixol-melitracen in the adjuvant therapy of ulcerative colitis is better than traditional drug treatments.